Back Cover: Electrolyte Mixtures Based on Ethylene Carbonate and Dimethyl Sulfone for Li‐Ion Batteries with Improved Safety Characteristics (ChemSusChem 11/2015). Issue 11 (5th June 2015) - Hofmann, Andreas; Migeot, Matthias; Thißen, Eva; Schulz, Michael; Heinzmann, Ralf; Indris, Sylvio; Bergfeldt, Thomas; Lei, Boxia; Ziebert, Carlos; Hanemann, Thomas
Abstract : The Back Cover picture shows the enhancement of thermal safety of Li‐ion battery cells by modification of the electrolyte solvent composition. The substitution of volatile linear organic carbonates by dimethyl sulfone leads to an improvement of the flash point of the electrolyte formulation to >140 °C. Surprisingly, both solvents (ethylene carbonate and dimethyl sulfone) are solid at room temperature, but the electrolyte mixture remains in liquid state at temperatures of as low as 0–5 °C. The improvement in thermal safety is schematically depicted in the form of pouch cell images whereas it has been proven for coin cells in the manuscript. However, it should be noted that the use of particle‐coated PET‐based separators additionally contributes to cell safety. More details can be found in the Full paper by Hofmann et al. (DOI: 10.1002/cssc.201500263 ).